Bioactive Molecules in Plant Defense Signaling in Growth and Stress - Jogaiah, Sudisha; Abdelrahman, Mostafa; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book focuses on signaling molecules in plant defense, outlining some of the most important cellular and chemical plant defense strategies during periods of stress and growth. Written by leading experts, it covers topics such as the diversity of plant-growth-promoting fungi, the gene-to-metabolite network of plant-microbe interactions, modulation of plant cellular responses to stress, and how plant nutritional deficiency affects crop production. Together with the companion volume Bioactive Molecules in Plant Defense: Saponins, this book offers an essential source of information for postgraduate students and researchers interested in plant pathology, mycology and sustainable agriculture.
Introduction -- Plant Growth Promoting Fungi: Diversity and Classification -- Microbial Signaling and Plant Growth Promotion -- Role of Elicitors in Plant Defense Signaling -- Plant-Microbe Interaction: Gene-to-Metabolite Network -- Phytohormones in the Modulation of Plant Cellular Responses to Stress -- Reactive Oxygen Species Generation-Scavenging and Signaling -- Lipoxygenase Signaling in Plant Defense -- Alkaloid Role in Plant Defense -- Beta-Glucosidades as detonators of Plant Chemical Defense -- Plant Nutritional Deficiency and its Impact on Crop Production.
Keywords: Biotechnology; Botanical chemistry; Bioorganic chemistry; Botany; Fungi; Mycology; Microbiology; Agriculture; Biotechnology; Plant Biochemistry; Bioorganic Chemistry; Plant Science; Fungi; Agriculture